Binder Jet 3D Printing of Compound LEV-PN Dispersible Tablets: An Innovative Approach for Fabricating Drug Systems with Multicompartmental Structures - Xiaoxuan Hong; Xiaolu Han; Xianfu Li; Jiale Li; Zengming Wang; Aiping Zheng (MDPI AG, 2021)
Three-dimensional (3D) printing is an emerging technology that has high application potential for individualized medicines and complex solid dosage forms. This study is designed to explore binder jet 3D printing (BJ-3DP) for the development of high-precision and repeatable compound levetiracetam-pyridoxine hydrochloride (LEV-PN) multicompartmental structure dispersible tablets. PN was dissolved in printing ink directly and accurately jetted into the middle, nested layer of the tablet, and precise control of the drug dose was achieved through the design of printing layers. With modification of the drying method, the "coffee ring" effect caused by drug migration during the curing and molding of the tablets was overcome. Furthermore, 3D topography showed that the tablets have a promising surface morphology. Scanning electron microscopy and porosity results indicated that the tablets have a loose interior and tight exterior, which would ensure good mechanical properties while enabling the tablet to disintegrate quickly in the mouth and achieve rapid release of the two drugs. This study used BJ-3DP technology to prepare personalized multicompartmental structures of drug systems and provides a basis for the development of complex preparations.